2000
DOI: 10.2460/javma.2000.216.1450
|View full text |Cite
|
Sign up to set email alerts
|

Herd-level risk factors for infection with Mycobacterium paratuberculosis in US dairies and association between familiarity of the herd manager with the disease or prior diagnosis of the disease in that herd and use of preventive measures

Abstract: Risk factors associated with Johne's disease in this study confirmed those management practices generally recommended for disease control. An educational problem, however, is the finding that herd managers familiar with Johne's disease generally use management practices similar to those used by managers unfamiliar with the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
121
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(138 citation statements)
references
References 16 publications
11
121
6
Order By: Relevance
“…Nevertheless, we expected to find a higher proportion of MAP-positive animals (by ELISA, as well as, by fecal culture and PCR) in the study herd, considering inappropriate herd management practices present and known to be risk factors for the disease (e.g. presence of animals born at other dairies, exposure of calves 0-6 weeks to adults feces, feces spread on forage fed to any age group (Collins et al, 1994;Goodger et al, 1996;Jakobsen et al, 2000;Wells and Wagner, 2000;Diéguez et al, 2008;Tiwari et al, 2009;Sorge et al, 2012;Künzler et al, 2014;Fernández-Silva and Ramírez-Vásquez, 2015;Vilar et al, 2015). When a test combination is considered, it must be taken into account that some infected cows produce antibodies for several years prior to the fecal-shedding of detectable quantities of MAP.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we expected to find a higher proportion of MAP-positive animals (by ELISA, as well as, by fecal culture and PCR) in the study herd, considering inappropriate herd management practices present and known to be risk factors for the disease (e.g. presence of animals born at other dairies, exposure of calves 0-6 weeks to adults feces, feces spread on forage fed to any age group (Collins et al, 1994;Goodger et al, 1996;Jakobsen et al, 2000;Wells and Wagner, 2000;Diéguez et al, 2008;Tiwari et al, 2009;Sorge et al, 2012;Künzler et al, 2014;Fernández-Silva and Ramírez-Vásquez, 2015;Vilar et al, 2015). When a test combination is considered, it must be taken into account that some infected cows produce antibodies for several years prior to the fecal-shedding of detectable quantities of MAP.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the odds of being JD-positive is greater for larger herds than for smaller herds [30,38]. Furthermore, farms that purchase stock from other farms are more likely to be positive than farms that do not purchase stock (closed herds) [30,31].…”
Section: Etiology and Epidemiologymentioning
confidence: 99%
“…Furthermore, farms that purchase stock from other farms are more likely to be positive than farms that do not purchase stock (closed herds) [30,31].…”
Section: Etiology and Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Economic losses attributable to PTB are a result of premature culling, reduced milk production, and loss of body weight in cattle sold for slaughter (Wells and Wagner, 2000). Dufour et al (2004) classified the losses attributable to PTB into two groups:…”
Section: Various Methods Of Estimation Of Economic Lossesmentioning
confidence: 99%